Nilai Perusahaan dalam Perspektif Keberlanjutan: Kajian Literatur atas Carbon Emission Disclosure dan Green Intellectual Capital pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia - Khairunnisa, Salma; Busra, Busra (Jurnal Riset Akuntansi Soedirman, 2025)
This study aims to examine the effect of carbon emission disclosure (CED) and green intellectual capital (GIC) on firm value from a sustainability perspective. The primary objective is to determine the extent to which carbon emission disclosure and the implementation of environmentally focused intellectual capital influence the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This research employs a quantitative approach using a causal associative method to measure cause-and-effect relationships between variables. The sample was selected using purposive sampling, focusing on companies that publish annual reports and sustainability reports and disclose data related to carbon emission disclosure and green intellectual capital.The data used are secondary data obtained from the official IDX website and the respective company websites. Firm value is measured using the Tobin's Q ratio, carbon emission disclosure is measured based on the disclosure index developed by Choi et al. (2013), and green intellectual capital is assessed through the components of green human capital, green structural capital, and green relational capital. The analysis was conducted using multiple linear regression with the help of SPSS software.The results indicate that the residual data are normally distributed and that the regression model meets classical assumptions. Hypothesis testing shows that carbon emission disclosure has no significant effect on firm value, with a probability value of 0.4350. In contrast, green intellectual capital has a significantly positive effect on firm value, with a coefficient of 0.808346 and a probability of 0.0000.